Kebijakan Pemerintah Terkait Larangan Impor Baju Bekas (Analisis Framing pada Tempo.co dan Media Indonesia) - Zain, Herlina Muzanah; Agustin, Dinar Ayu Chandra (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
AbstractThis research aims to analyze the framing of government policy reporting regarding the Prohibition of Importing Used Clothes on Kompas.co and Media Indonesia. This research is based on the Government Policy regarding the ban on the import of used clothes which has become a public topic of conversation again after President Jokowi made his statement regarding the ban on the import of used clothes because it was considered detrimental to the local fashion industry or MSMEs. Reports related to this policy enlivened the news in online media, especially in the online media Tempo.co and Media Indonesia. The aim of this research is to see how the two online media above frame the news about government policy regarding the ban on importing used clothes on Kompas.co and Media Indonesia using the framing analysis model. Robert N. Entman divides the framing device into four elements: Define Problems, Diagnose Causes , Make Moral Judgment, Treatment Recommendation. Overall, news articles on Tempo.co and Media Indonesia focus on the government's efforts to resolve the problem of importing used clothes which are framed in the form of government actions and policies. The news on Tempo.co and Media Indonesia also provides information about policies related to the ban on importing used clothes, from actions to legal regulations, as well as the negative consequences of allowing import activities to continue.Keywords: Policy, Import, Used Clothes, Framing. Abstraksi Penelitian ini ingin menganalisis mengenai framing pemberitaan kebijakan pemerintah terkait Larangan Impor Baju Bekas di Kompas.co dan Media Indonesia. Penelitian ini didasarkan pada adanya Kebijakan Pemerintah terkait larangan impor baju bekas yang kembali menjadi perbincangan publik setelah Presiden Jokowi memberikan pernyataannya terkait larangan impor baju bekas karena dianggap merugikan industri fashion lokal atau UMKM. Pemberitaan terkait kebijakan tersebut meramaikan pada pemberitaan di media online khususnya pada media online Tempo.co dan Media Indonesia. Tujuan dari penelitian ini untuk dapat melihat bagaimana kedua media online diatas membingkai pemberitaan tentang Kebijakan pemerintah terkait larangan impor baju bekas di Kompas.co dan Media Indonesia dengan menggunakan model analisis framing Robert N. Entman membagi perangkat framing ke dalam empat elemen Define Problems, Diagnose Causes, Make Moral Judgement, Treatment Recommendation. Secara keseluruhan, artikel berita di Tempo.co dan Media Indonesia berfokus pada upaya pemerintah untuk menyelesaikan masalah impor baju bekas yang dibingkai dalam bentuk tindakan dan kebijakan pemerintah. Berita di Tempo.co dan Media Indonesia tersebut juga memberikan informasi tentang kebijakan yang terkait dengan larangan impor baju bekas, mulai dari tindakan, peraturan perundang-undangan, serta konsekuensi negatif dari membiarkan kegiatan impor berlanjut.Kata Kunci: Kebijakan, Impor, Baju Bekas, Framing